AAA Rupture and Psoas Hematoma due to Type II Endoleak from Inferior Mesenteric Artery “Unusual” Collaterals - Panagiotis G. Theodoridis; Dimitrios N. Staramos; Nikolaos Ptochis; Ioannis A. Papailiou; Ilias Dodos; Nikolaos Iatrou; Anastasios G. Potouridis; Konstantinos Dervisis (Case Reports in Vascular Medicine)
Although endovascular aneurysm repair (EVAR) in the abdominal aorta has reduced the perioperative mortality when compared with open repair, the need for reintervention after complications such as endoleak may be presented in up to 20% of the cases. Type II endoleak from branch vessels is often benign but can potentially be associated with progressive abdominal aortic aneurysm growth and sac expansion. We present a rare case of a patient who presented with sac expansion and psoas hematoma due to Type II endoleak from “unusual” collaterals of IMA and was treated successfully with endoleak microembolization and percutaneous decompression of the hematoma.